The Kentucky Thoroughbred. - Hollingsworth, Kent (University Press of Kentucky, 2011)
Kent Hollingsworth captures the flavor and atmosphere of the Sport of Kings in the dramatic account of the development of the Thoroughbred in Kentucky. Ranging from frontier days, when racing was conducted in open fields as horse-to-horse challenges between proud owners, to the present, when a potential Triple Crown champion may sell for millions of dollars, The Kentucky Thoroughbred considers ten outstanding stallions that dominated the shape of racing in their time as representing the many eras of Kentucky Thoroughbred breeding. No less colorful are his accounts of the owners, breeders, trai.